A statistical quality control study on Universal Steel Smelting Co., Inc. - Balagtas, Paula Marie (College of Engineering, 2002)
Universal Steel Smelting Co. Inc. is a producer of reinforcing steel bars, which is used for construction of roads, column supports and walls. These steel bars come in different diameter sizes : 12 mm, 16 mm, 20 mm, 25 mm, 28 mm, 30 mm, and 36 mm. The processes involved in making these steel bars are primarily smelting of the billets to rolling operations to reduce the cross-section of the bars to the desired size. Rolling operations form the bulk of the operations of the company in producing the steel bars. These operations form numerous waste materials due to poor handling of the raw materials to the incorrect processing of the work-in-process to improper finishing operations in the cooling bed. These wastage or scrap, as commonly referred to by the company, can be classified into three categories : Mis-rolled bars, Crop Shear Ends, and Bar Ends. Now, the group attacked these three quality problems addressing the top-three product sizes with respect to rejects generated (16 mm-G33, 12mm-G33, and 12mm-G40): For the Misrolled bars, it was found out that the clearance of the dies which is controlled by the screws affect the occurence of this type of wastage. The Statistical Process Control Chart used was a cusum plot, although there were no out-of-control points obtained the group proposed to record each setting of the screws permanently to be consistent and to aid in the monitoring of this cause of rejects. This can minimize unwanted variability in the product so as to reduce the occurence of the misrolled bars for the process. Regarding the Crop Shear ends, it was also found that this type of wastage is dependent upon the alignment of the roll bars with the rolling guides on the rolling mill. The control chart posted the first four points to be out-of-control which gives a shift from the process mean of 0.007 to 0.0195 and is attributable to the mentioned cause. To address this problem it was found out that most of the changes in die contributes to the wear of the screws holding the roll balls and guides in place. It was also suggested that replacement of these alignment screws be done in the earliest possible time so as to avoid greater loss of materials that could spell a lot of savings for the company. On the Bar ends type of wastage the group was able to pinpoint its cause, the non-uniform cutter feed rate as the culprit. Also through the use of the cusum chart, the out-of-control point in the second period gave a shift in process mean from 0.02 to 0.0385 attributing it to the assignable cause above. In addressing this problem it was noted that the cutter itself is semi-automatic and is a function of time and speed, therefore to minimize variability in the feed rate it is necessary to perform calibration of the cutter feed rate more often. And that the cutting edge be kept sharp to maintain constant cutting time for the steel bars. In the Process Capability section, it was found that the actual rolling process for the 16mm-G33 size yielded a Process Capability Ratio of 0.7019 which is low for the process with an upper limit of 2.00. This gives Process average fallout of 1.54 percent and Uses 142.47 percent of its tolerance band. For the 12mm-G33 and 12mm-G40 sizes the PCR are computed to be 0.0997 and 0.1811 respectively, which are also very low. Therefore it leads to high Process Average Fallout, 38.59 percent and 29.36 respectively and uses more than 100 percent of its tolerance bands, 1003 percent for 12mm-G33 and 552.18 percent for 12mm-G40. This means that the actual rolling process is not capable to meet the specified limits. On top of these three quality-related problems the group addressed the mode of selling of the scrap materials of the company. To address this problem there are two proposed solutions : to sell scrap as is, and to rework it then sell it. Based on the study made the best alternative is to sell the scrap materials as is, as this would give the company an operating profit of Php72,992.936 for its scrap material and upset the loss due to these scrap. However the rework alternative needs to be studied further as stated.